Combination immunotherapy and anti-angiogenic therapy shows promising efficacy in NSCLC patients with recurrent or refractory brain metastases and negative driver genes - Sun, Liwei; Chen, Bonian; Wang, Bin; Li, Jinduo; Li, Lin; Tian, Caijuan; Zhang, Hongbo; Liu, Pengfei; Liu, Xiaomin (Frontiers in Immunology, 2025)
IntroductionThis study aimed to evaluate the efficacy of immunotherapy combined with anti-angiogenic therapy for non-small cell lung cancer (NSCLC) with brain metastasis (BM) and negative driver genes.MethodsThis observational prospective study was conducted using the clinical data of 34 patients with NSCLC and BM, including 24 patients who received immunotherapy combined with anti-angiogenic therapy and 10 control patients using oral anlotinib upon the first- to fourth-line treatment failure or refusing to continue chemotherapy between June 2017 and August 2022. Efficacy was evaluated using progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and adverse reactions.ResultsAmong 24 patients treated with immunotherapy combined with anti-angiogenic therapy, 17 had a partial response, six had stable disease, and one had progressive disease. The ORR and DCR of patients receiving immunotherapy combined with anti-angiogenic therapy were 70.8% and 95.8%, respectively. The median PFS of immunotherapy combined with anti-angiogenic treatment was significantly longer than that of oral anlotinib (18.0 vs. 4 months, log-rank test, p < 0.0001), indicating that immunotherapy combined with anti-angiogenic therapy can substantially improve the treatment efficacy for NSCLC with BM and negative driver genes. Adverse reactions mainly included rash in one case and hypothyroidism in one case, but did not involve myocardial damage or liver and kidney function damage.ConclusionImmunotherapy combined with anti-angiogenic therapy in patients with recurrent or refractory NSCLC and BM driven by negative genes has yielded promising but preliminary findings.Clinical Trial Registrationwww.chictr.org.cn, identifier ChiCTR1800017499